2021
DOI: 10.3389/fimmu.2021.627568
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-Seronegative Subjects Target CTL Epitopes in the SARS-CoV-2 Nucleoprotein Cross-Reactive to Common Cold Coronaviruses

Abstract: The beta-coronavirus SARS-CoV-2 induces severe disease (COVID-19) mainly in elderly persons with risk factors, whereas the majority of patients experience a mild course of infection. As the circulating common cold coronaviruses OC43 and HKU1 share some homologous sequences with SARS-CoV-2, beta-coronavirus cross-reactive T-cell responses could influence the susceptibility to SARS-CoV-2 infection and the course of COVID-19. To investigate the role of beta-coronavirus cross-reactive T-cells, we analyzed the T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Longitudinal studies suggest that HCoVs induce a stable pool of memory CD4+ T cells that may account for the FluoroSpot IFN-γ responses in participants with no prior COVID-19 infection [ 63 ]. Cross-reactive epitopes present in SARS-CoV-2 and other HCoVs have been identified in the S, N and M proteins [ 46 , 61 , 64 66 ], including within the Sp6 and Mp1 subpools.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies suggest that HCoVs induce a stable pool of memory CD4+ T cells that may account for the FluoroSpot IFN-γ responses in participants with no prior COVID-19 infection [ 63 ]. Cross-reactive epitopes present in SARS-CoV-2 and other HCoVs have been identified in the S, N and M proteins [ 46 , 61 , 64 66 ], including within the Sp6 and Mp1 subpools.…”
Section: Discussionmentioning
confidence: 99%
“…Nethertheless, these data indicate that T-cell responses raised against these peptides may cross react with future SARS-CoV-2 variants, which may evolve to escape neutralising antibody responses, and against future emerging coronaviruses. This is supported by studies screening SARS-CoV-2 epitopes in COVID-19 and uninfected patients which have observed SARS-CoV-2 epitopes specific CD4+ and CD8+ T cell responses in SARS-CoV-2 uninfected individuals, which share homology with epitopes in other human coronaviruses [6, 8–10, 31]. The SARS-CoV-2 peptides studied here include 125 epitopes identified by these epitope screening studies of SARS-CoV-2 patients [6, 8, 9, 19, 31, 32].…”
Section: Discussionmentioning
confidence: 60%
“…This is supported by studies screening SARS-CoV-2 epitopes in COVID-19 and uninfected patients which have observed SARS-CoV-2 epitopes specific CD4+ and CD8+ T cell responses in SARS-CoV-2 uninfected individuals, which share homology with epitopes in other human coronaviruses [6, 8–10, 31]. The SARS-CoV-2 peptides studied here include 125 epitopes identified by these epitope screening studies of SARS-CoV-2 patients [6, 8, 9, 19, 31, 32]. A recent study, screening epitopes in 16 COVID-19 patients identified 122 epitopes reactive to T-cells in these individuals [33].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Functional proteins were not considered since some of them are known to hijack MHC systems in human (25, 26, 27). There are numerous studies now for homology of nucleocapsid protein sequences between COVID and HuCoV strains (18, 28, 29, 30, 31). Also, T-cell response of COVID unexposed individuals to COVID was observed for at least one peptide from envelope protein (32) indicating potential effect from common cold immunity.…”
Section: Introductionmentioning
confidence: 99%